Benthic foraminifera as bio-indicators of chemical and physical stressors in Hammerfest harbor (Northern Norway). Issue 1 (15th January 2017) - Dijkstra, Noortje; Junttila, Juho; Skirbekk, Kari; Carroll, JoLynn; Husum, Katrine; Hald, Morten
Abstract: We investigated benthic foraminiferal assemblages in contaminated sediments in a subarctic harbor of Northern Norway to assess their utility as indicators of anthropogenic impacts. Sediments in the harbor are repositories for POPs and heavy metals supplied through discharges from industry and shipping activities. Sediment contaminant concentrations are at moderate to poor ecological quality status (EcoQS) levels. The EcoQS based on benthic foraminiferal diversity reflects a similar trend to the EcoQS based on contaminant concentrations. Foraminiferal density and diversity is low throughout the harbor with distinct assemblages reflecting influence of physical disturbances or chemical stressors. Assemblages impacted by physical disturbance are dominated by L. lobatula and E. excavatum, while assemblages impacted by chemical stressors are dominated by opportunistic species S. fusiformis, S. biformis, B. spathulata and E. excavatum . The foraminiferal assemblage from an un-impacted nearby fjord consists mainly of agglutinated taxa. These assemblages provides a valuable baseline of the ecological impacts of industrialization in northern coastal communities. Highlights: Physical, chemical and organic pollution are distinguished as dominant stressors. Sediment contaminant concentrations reflect chronic to acute ecosystem impacts. Two benthic foraminiferal assemblages were distinguished reflecting main stressors. Organic pollution resulted in no living and low number fossilized tests. The assemblage from an un-impacted reference site shows natural harsh conditions.